Mechanical and thermal properties of biodegradable composite from kenaf fibre and polylactic acid polymer / Wan Nor Raihan Wan Jaafar - Wan Jaafar, Wan Nor Raihan (Institute of Graduate Studies, UiTM, 2017)
Natural fibre (kenaf fibre) reinforced natural polymer, polylactic acid (PLA) was used for production of composites, where end life disposal is harmful to human and environment and able to self degraded. It is due to abundance of solid waste accumulation especially from plastic materials that seriously has taken numerous attentions. Kenaf bast and core fibre was separated and treated similarly to reinforce PLA. The effect of preparation condition such as acid hydrochloric concentration, extrusion rotation speed and amount of fibre loading was used to investigate composites properties. While the effect of natural weathering and landfill burial on composites properties was investigated for its degradation. Kenaf fibre was treated at 6% w/w NaOH followed by various HCl concentrations (0.5 M, 1.0 M, and 1.5 M). Fibres were then cryocrushed to reduce size and compounded with PLA at various rotation speed (60, 70, and 80 rpm) and fibre loading (2, 4, and 6%) to determine the optimum parameter. Mechanical properties (flexural and impact), thermal properties (TGA and DSC), microscopic observation (SEM and TEM), Fourier Transform Infra-Red (FTIR), X-Ray Diffraction (XRD) were done for the investigation of the composites properties…